Resolving the controversies about the 'nearly cubic' and other phases of Sr1-xCaxTiO3 (0≤x≤1): II. Comparison of phase transition behaviours for x ≤ 0.40 and 0.43 - Mishra S.K.; Ranjan R.; Pandey D.; Ranson P.; Ouillon R.; Pinan-Lucarre J.-P.; Pruzan P. (My University, 2025)
The phase transition behaviour of two 'nearly cubic' compositions, x ≤ 0.40 and 0.43, of Sr1-xCaxTiO3, representative of Pbnm and Pbcm space group structures, has been investigated using temperature dependent dielectric, x-ray diffraction and Raman scattering techniques. For x ≤ 0.40, a first order antiferroelectric phase transition occurs around 364 K followed by an antiferrodistortive phase transition involving the R point () instability at ∼800 K. For x ≤ 0.43, on the other hand, there is no antiferroelectric phase transition. Instead, two antiferrodistortive transitions around 463 and 850 K linked with the M () and R () point instabilities, respectively, are observed. Both the compositions also exhibit qualitatively different types of phase transitions below room temperature. Evidence for a new phase transition at low temperatures is presented for x ≤ 0.43. © 2006 IOP Publishing Ltd.